Life and Policy Disconnect of Construction Labourers in Ludhiana City (Punjab, India) - Jha, Kunal; Gavsker, Kapil Kumar (Geographical Journal of Nepal, 2026)
Rapid urbanisation and industrialisation have fuelled the growth of informal labour markets in Indian cities, with the construction sector absorbing a significant share of unskilled migrant workers. This study explores the living and working conditions of construction labourers in Ludhiana City, Punjab, and examines their living and work conditions and their disconnect from policies. Using the snowball sampling method, primary data were collected through a field survey and personal interviews with 120 construction labourers across three identified streams of employment: labour chowks, large-scale construction project sites, and private building sites. Focus group discussions were first conducted to map the channels through which labourers enter the job market, followed by structured interviews with key open-ended questions. The results reveal that the surveyed labourers earn an average monthly wage of only US$ 113.19, with 79.16% residing in rented accommodations. A majority (62.5%) lack any formal training in construction work, 69.16% do not possess identity proof with their current address, and none of the surveyed labourers was registered under the Building and Other Construction Workers Act, 1996. The labourers remain almost entirely unaware of welfare schemes designed for them. The study concludes that construction labourers live and work in distressful conditions, systematically excluded from social security frameworks, and calls for urgent policy interventions, including grassroots outreach, mandatory registration mechanisms, and employer accountability to bridge this welfare gap.